Autotaxin Derived From Lipoprotein(a) and Valve Interstitial Cells Promotes Inflammation and Mineralization of the Aortic Valve. Issue 8 (25th August 2015) - Bouchareb, Rihab; Mahmut, Ablajan; Nsaibia, Mohamed Jalloul; Boulanger, Marie-Chloé; Dahou, Abdellaziz; Lépine, Jamie-Lee; Laflamme, Marie-Hélène; Hadji, Fayez; Couture, Christian; Trahan, Sylvain; Pagé, Sylvain; Bossé, Yohan; et al.
<x xml:space="preserve">Abstract</x> Background— Mendelian randomization studies have highlighted that lipoprotein(a) [Lp(a)] was associated with calcific aortic valve disease (CAVD). Lp(a) transports oxidized phospholipids with a high content in lysophosphatidylcholine. Autotaxin (ATX) transforms lysophosphatidylcholine into lysophosphatidic acid. We hypothesized that ATX-lysophosphatidic acid could promote inflammation/mineralization of the aortic valve. Methods and Results— We have documented the expression of ATX in control and mineralized aortic valves. By using different approaches, we have also investigated the role of ATX-lysophosphatidic acid in the mineralization of isolated valve interstitial cells and in a mouse model of CAVD. Enzyme-specific ATX activity was elevated by 60% in mineralized aortic valves in comparison with control valves. Immunohistochemistry studies showed a high level of ATX in mineralized aortic valves, which colocalized with oxidized phospholipids and apolipoprotein(a). We detected a high level of ATX activity in the Lp(a) fraction in circulation. Interaction between ATX and Lp(a) was confirmed by in situ proximity ligation assay. Moreover, we documented that valve interstitial cells also expressed ATX in CAVD. We showed that ATX-lysophosphatidic acid promotes the mineralization of the aortic valve through a nuclear factor κB/interleukin 6/bone morphogenetic protein pathway. In LDLR–/–/ApoB100/100/IGFII mice, ATX is overexpressed and lysophosphatidic acid promotes a strong deposition of hydroxyapatite of calcium in aortic valve leaflets and accelerates the development of CAVD. Conclusions— ATX is transported in the aortic valve by Lp(a) and is also secreted by valve interstitial cells. ATX-lysophosphatidic acid promotes inflammation and mineralization of the aortic valve and thus could represent a novel therapeutic target in CAVD.